20.5k views
0 votes
Which expression is equivalent to the following complex fraction?

Which expression is equivalent to the following complex fraction?-example-1
User Krummens
by
5.7k points

1 Answer

6 votes

Answer:

Second Option: = 2(y-2x)/(3y-5x)

Explanation:

The expression is:

=(2/x-4/y)/((-5)/y+3/x)

Taking LCM in both, numerator and denominator

= ((2y-4x)/xy)/((-5x+3y)/xy)

Since we know,

(a/b)/(c/d)=ad/bc

Applying the rule to the given fraction:

=(2y-4x)(xy)/(-5x+3y)(xy)

xy will be cancelled and we will be left with:

=(2y-4x)/(-5x+3y)

Taking 2 as common:

= 2(y-2x)/(3y-5x)

So the second option is the correct answer. ..

User Mikef
by
6.1k points